2018
DOI: 10.14196/mjiri.32.57
|View full text |Cite
|
Sign up to set email alerts
|

Association between tooth impaction and odontogenic lesions: A matched case-control study

Abstract: Background: Impacted tooth is common in dental practice. Dentists usually remove them if they are associated with any pathologic sign or symptom. The challenge is whether to extract the asymptomatic tooth or not. This study was conducted to determine the association between developmental odontogenic cysts and tumors and impacted and unerupted teeth, if left untreated. Methods: In this matched case-control study, 262 participants were recruited in case and control groups to evaluate the association between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Lower impacted 3Ms were found to be more likely to exhibit pathology than upper impacted teeth, a finding that supports previous studies. 23 37 40 In the maxilla, both the prevalence of impacted 3Ms (26.3%) and the occurrence of pathologic conditions (16.5%) were less frequent than in the mandible, for which the rates were 73.7% and 26.3%, respectively. As reported by Hounsome et al, 9 the prevalence of prophylactic extractions was considerably higher among upper 3Ms (79%) compared to lower 3Ms (22%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower impacted 3Ms were found to be more likely to exhibit pathology than upper impacted teeth, a finding that supports previous studies. 23 37 40 In the maxilla, both the prevalence of impacted 3Ms (26.3%) and the occurrence of pathologic conditions (16.5%) were less frequent than in the mandible, for which the rates were 73.7% and 26.3%, respectively. As reported by Hounsome et al, 9 the prevalence of prophylactic extractions was considerably higher among upper 3Ms (79%) compared to lower 3Ms (22%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those demographic variables have been the subject of investigation in previous studies. 10 12 32 40 …”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2018 revealed that lesions associated with impaction, including dentigerous cyst, OKC, and ameloblastoma in the mandible, had different prevalences of (46.6%), (29.8%), and (9.2%), respectively, and most of the impaction located in the mandible 26 . In this study (41.7%) of OKCs were associated with the impacted tooth, and were located in the mandible and (79.2%) of all the lesions had a welldefined border.…”
Section: Discussionmentioning
confidence: 99%
“…Although the decision to remove symptomatic third molars is a straightforward one, the prophylactic removal of asymptomatic third molars remains a controversial issue [15].…”
Section: Discussionmentioning
confidence: 99%